Why Indonesian Corporate Governance Failed–Conjectures Concerning Legal Culture - Tabalujan, Benny S. (Columbia Journal of Asian Law, 2002)
Indonesia, the fourth most-populous nation in the world, is one of the Asian countries still mired in deep economic problems. For Indonesia, the financial crisis that first hit the Asian region in mid-1997 quickly became a political and social crisis as well. Five years and four presidents later, Indonesia is just beginning to show some hopeful preliminary signs of economic recovery. My goal in this paper is to examine Indonesian corporate governance behavior leading up to the crisis during the 1990s and to discuss some lessons to be learned. This is because corporate governance failure has been highlighted as a key contributing factor to explain why Indonesia suffered so badly from the 1997-1999 crisis, compared to other Asian countries. If poor corporate governance is the culprit, then the more that is known about it the more likely a suitable remedy can be applied to solve the problem and to prevent its recurrence.